BELARUSSIAN CONSTRUCTION SCIENTIFIC AND TECHNICAL TERMINOLOGY - E. A. Moyseichik; A. V. Avdenia; E. E. Vovna; V. I. Zavadsky (Наука и техника, 2010)
The paper analyzes an experience of terminology development and standardization of construction technical normative and legal acts. The paper reveals methods for better qualitative development of terms for construction and indicates a necessity of their harmonization with the acts in Belarus.